The perception of students and educators on ethics education in the Diploma in Accountancy programme - Nor Sharizad bt Zainal Abidin (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2016)
Ethics has become of significant interest amongst practitioners and educators alike. The collapse of Enron, the largest energy-trading company in the United States has jolted the profession out of its complacency and serves as a warning that all is not well with the profession. The message is clear, if the accountants and future accountants want to be relevant, they have to be more diligent and ethical. In order to inculcate ethical behaviour, ethics education is important to increase awareness and enhance ethical behaviour in the profession, including amongst students. Ethical behaviour can be developed at an earlier stage of education. As a result, it is crucial for the Diploma in Accountancy programme to integrate ethics education. Thus, this study is to assist Majlis Amanah Rakyat (MARA) in improving the Diploma in Accountancy (DIA) programme in Kolej Profesional Mara (KPM) by gathering perception of students and educators on ethics education. Therefore, the objectives of the study are to determine and investigate (1) the perceptions of students and educators regarding the need for ethics education in the DIA programme (2) the students' and educators' reasons for integrating or not integrating ethics (3) the students' and educators' perceptions on the appropriate ways and techniques of teaching ethics and (4) the difference in perceptions between students and educators on ethics education in the DIA programme. Questionnaires were distributed to the DIA students and educators at four different colleges in order to collect the data on their perceptions on integrating ethics into the DIA programme. More than half of DIA students and educators agree that there is a need for ethics education in the programme. 'Failure to teach ethics in the accounting curricula contributes to the recent business scandals' is perceived as the main reason by students and educators for the need to integrate ethics education into the DIA programme. However, some of the students disagree to having ethics education due to the inadequacy of materials for teaching ethics. On the other hand, the educators perceived that the responsibility of encouraging ethical values should be left to parents and family members. In terms of techniques used in teaching ethics, students prefer to use vignettes followed by discussion through internet. Whereas educators prefer to organize ethics day and have a debate on ethics. Nevertheless, both students and educators generally agreed that ethics education should be integrated into the DIA programme and at the same time, educators need to improve their knowledge and techniques in teaching ethics. The implication of the study is to enhance ethics education in the DIA programme.